Co-exposure of polyvinyl chloride microplastics with cadmium promotes nonalcoholic fatty liver disease in female ducks through oxidative stress and glycolipid accumulation - Chen, Yan; Jin, Hengqi; Ali, Waseem; Zhuang, Tinglong; Sun, Jian; Wang, Tao; Song, Jie; Ma, Yonggang; Yuan, Yan; Bian, Jianchun; Liu, Zongping; Zou, Hui (Poultry science, 2024)
A recently discovered environmental contaminant, microplastics (MP) are capable of amassing within the body and pose a grave threat to the health of both humans and animals. It is widely acknowledged that the combination of cadmium (Cd), a hazardous heavy metal, and microplastics produces synergistic deleterious effects. Nevertheless, the mechanism by which co-exposure to polyvinyl chloride microplastics (PVC-MP) and Cd damages the liver of avian females is unknown. Globally prevalent and the subject of extensive research in mammals, nonalcoholic fatty liver disease (NAFLD) is a chronic liver condition. However, the mechanisms underlying injury to the avian digestive system caused by NAFLD remain unknown. Two months of co-exposure to Cd and PVC-MPs, pure water, solitary Cd exposure, single microplastics exposure, and pure water were administered to female Muscovy ducks in this study. The objective of this research was to examine whether the co-exposure of duck liver to PVC-MPs and Cd-induced oxidative stress resulted in NAFLD and subsequent apoptosis of hepatic cells. The study's findings showed that hepatocyte shape and functional activity were negatively impacted by PVC-MP and Cd buildup in liver tissues. Reduced liver organ coefficients, increased alanine aminotransferase (ALT) content, and ultrastructural damage to hepatocyte nuclei and mitochondria are indicators of this. These results point to a possible impairment in liver function. phosphoenolpyruvate carboxykinase 1 (PCK1) deficiency activates the protein kinase B/phosphatidylinositol 3-kinase (PI3K/AKT) pathway in the livers of female reproductive ducks that have been damaged by oxidative stress. This stimulation induces lipid deposition, fibrosis, and glycogen accumulation, which ultimately results in hepatocyte apoptosis. In summary, our research provides evidence that PVC-MPs cause oxidative harm to the liver, which subsequently results in fibrosis of liver tissue, hepatic glucolipid metabolism, and ultimately apoptosis.